Assessment of emotional intelligence level in intercultural educational environment - T. V. Kuprina; A. A. Evtyugina; S. M. Minasyan; O. V. Taranova (Russian State Vocational Pedagogical University, 2022)
Introduction. Currently, the training of professionally competent specialists is a priority in the higher education system. One of the productive creative approaches is the development of emotional intelligence (EI/EQ), which contributes to the development of emotional intercultural competence to accelerate adaptation in a new intercultural environment.Aim. The aim of the research is to empirically determine the level of emotional intelligence in the intercultural context for further improving work with students of the humanities and economics specialities and proposing new techniques that develop emotional intercultural competence.Methodology and research methods. The methodological basis of the research is the concept of developing emotional intelligence as an integral part of soft skills. To study the level of emotional intelligence, the authors used the Mark Daniel Self-Scoring Emotional Intelligence Tests, which are a compilation of tests designed to study the level of emotional intelligence and determine the strengths and weaknesses of the test takers. The methods of psycho-diagnostics, comparison and generalisation of the obtained results were used. The test results were analysed using the SPSS.27 statistical package.Results. The research results help to understand the psychological characteristics of students of the humanities and economics specialities, taking into account the cultural context, which makes it possible to predict the difficulties and problems faced by teachers in the process of work with this type of students, to more accurately determine the characteristics and motives of their behaviour and the characteristics of the professional development of the individual. It also helps to select the right curriculum to meet students' needs.Scientific novelty. The scientific novelty of the research consists in supplementing the existing knowledge in the field of EI about the psychological characteristics of representatives of the humanities and economics specialities in the context of intercultural communication and further forecasting their development based on correctly selected teaching methods.Practical significance. The presented features of students of the humanities and economics specialities can be employed by teachers when interacting with them and organizing the educational process, taking into account their interests and needs, as well as adjusting the level of development of EI. The results obtained can be useful in the preparation of educational and methodological complexes specifically designed for the development of emotional intercultural competence.